Cortical motor representation of the rectus femoris does not differ between the left and right hemisphere. (June 2016) - Ward, Sarah; Bryant, Adam L.; Pietrosimone, Brian; Bennell, Kim L.; Clark, Ross; Pearce, Alan J.
Abstract: Transcranial magnetic stimulation (TMS) involves non-invasive magnetic stimulation of the brain, and can be used to explore the corticomotor excitability and motor representations of skeletal muscles. However there is a lack of motor mapping studies in the lower limb and few conducted in healthy cohorts. The cortical motor representations of muscles can vary between individuals in terms of center position and area despite having a general localized region within the motor cortex. It is important to characterize the normal range for these variables in healthy cohorts to be able to evaluate changes in clinical populations. TMS was used in this cross-sectional study to assess the active motor threshold (AMT) and cortical representation area for rectus femoris in 15 healthy individuals (11 M/4F 27.3 ± 5.9 years). No differences were found between hemispheres (Left vs. Right P  = 0.130) for AMT. In terms of y -axis center position no differences were found between hemispheres (Left vs. Right P  = 0.539), or for the x -axis center position (Left vs. Right P  = 0.076). Similarly, no differences in calculated area of the motor representation were found (Left vs. Right P  = 0.699) indicating symmetry between hemispheres.